Persepsi Siswa terhadap Game Baamboozle dalam Meningkatkan Motivasi Pembelajaran Bahasa Arab - Damawiyah, Siti Asiah; Ghufron, Zaki; Indriana, Dina; Ubaidilllah, Ubaidillah (AS-SABIQUN, 2025)
This study is motivated by the lack of motivation and interest of students in learning Arabic, which is caused by the use of monotonous learning media and the lack of utilization of digital media. The purpose of this study is to measure students' perceptions by using Baamboozle game media on students' learning motivation in learning Arabic. The method used was a quantitative survey involving 55 respondents from several Madrasah Tsanawiyah in Serang Regency. The instrument used was a Likert questionnaire to measure students' learning motivation, and data were collected through observation and questionnaires after the implementation of the game in learning. The results showed that the use of Baamboozle game significantly increased students' learning motivation by 51% with a high positive response to the more interactive and fun learning. In addition, students feel more enthusiastic and involved in the learning process. In conclusion, the application of game-based learning media such as Baamboozle can be an effective strategy to increase students' motivation and engagement in learning Arabic, as well as creating a more dynamic learning atmosphere.